In-depth assessment of structural and mechanical properties of copper slag as an eco-friendly alternative construction material - Noufal, E. Rahmathulla; Kasthurba, A.K.; Sudhakumar, J.; Manju, Unnikrishnan (Journal of Structural Engineering, 2024)
Two significant problems that require immediate attention are (i) the rising demand for building materials to meet the expanding demands of the construction industries, and (ii) the rising production of industrial wastes that must be properly disposed of as a result of rapid industrialization and growing urbanization. Therefore, researchers have been working continuously to find solutions to these issues and have been investigating the potential uses of industrial waste slags as an alternative, sustainable construction material. Given that the slags can vary in their chemical compositions and may contain large concentrations of heavy metals, rendering them toxic and dramatically modifying their properties, a comprehensive study of the slag attributes is crucial in this context. As a substitute for river sand as fine aggregate in reinforced cement concrete, copper slag, a byproduct of copper smelting and refining, is discussed in detail here in terms of its structural, mechanical, physical, and chemical qualities. In order to determine the electronic structure, surface atomic concentrations, and phase analysis of the slag concrete, X-ray photoemission spectroscopy analysis, powder X-ray diffraction measurements, direct shear analysis, ultrasonic pulse velocity analysis, and rapid chloride permeability tests were conducted.